Cía. minera Milpo S.A.A.: valorización de una empresa minera - Mendiola Cabrera, Alfredo (2007)
Bailey Investments Inc. (BII) was restructuring their investment portfolio and examining the possibility of extending their exposure towards the Peruvian mining industry. Specifi cally, they were interested in investing in the Milpo Mining Company, about which they had very good references. For this reason, they asked MC Peru, who is one of their primary foreign customers, to create a report about the convenience for realizing this investment. They expected a comparison between the market price and the value of ordinary Milpo stock. Analyst Ernesto Valdez, who was in charge of this work, knew that he would only have a short time (three days) to do so, meaning that there would not be any time to converse with Milpo representatives, and his analysis would have to focus on public information available through the Internet.